Validation of the Japanese version of the Kenny Music Performance Anxiety Inventory-Revised - Takagi, Sakie; Yoshie, Michiko; Murai, Akihiko (Frontiers in Psychology, 2025)
The Japanese version of the Kenny Music Performance Anxiety Inventory-Revised (K-MPAI-R) has been developed but not yet been validated. This study aims to validate and certify the Japanese version of the K-MPAI-R. Data were collected from 400 participants (250 men, 149 women, and one identifying as other), aged between 18 and 64 years (M = 46.84, SD = 10.45). The sample included 200 professional and 200 amateur musicians, comprising 309 instrumentalists and 91 vocalists. An exploratory factor analysis with promax rotation extracted seven factors that explained 55.8% of the total variance, demonstrating a structure similar to the original version. The scale showed high internal consistency, with a Cronbach's alpha of 0.93. Criterion-related validity was supported by correlations with the State-Trait Anxiety Inventory (r = 0.67) and Performance Anxiety Questionnaire (r = 0.75). These findings indicate that the Japanese version of the K-MPAI-R is a reliable and valid measure of music performance anxiety. This validated instrument enables further investigations into music performance anxiety among Japanese musicians.